PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH TERHADAP PELAKSANAAN PERATURAN DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2004 TENTANG PEMERINTAHAN DAERAH - Setya, Kartika Winkar (MIH FH UNSOED, 2015)
Indonesia is a unitary state which is divided into provincial areas which are further subdivided into areas of the district/city based on the principle of regional autonomy. The existence of local regulation is very important, but unfortunately there are a variety of problematic regulations that live in the society, either because it does not conform with the conditions of the society or for not complying with legislation is another. Local regulations are problematic it can be minimized by monitoring function held by Parliament, as mentioned in Article 42 paragraph (1) letter c of Act No. 32 of 2004 which stipulates that Parliament has the duty and authority to supervise the implementation of local regulations. Supervision by the Provincial Council and District Council carried out local regulation on the implementation by the Act 32 of 2004 uses the concept of supervision in the narrow sense that focused on matching between rules and their implementation in the field. Parliament in the means used to supervise the implementation of regulations in general through the implementation of the rights of Parliament, implementation consulting, receiving complaints and aspirations of the people. Yet there are clear arrangements regarding the parameters of supervision, monitoring and corrective action mechanisms of monitoring the implementation by the parliament.Keyword: local governments, local regulations, supervision